Government grants: aspect of accounting according to international standards - Olena Lagovska; Олена Лаговська; Gabriella Loskorikh; Лоскоріх Габріелла; Loszkorih Gabriella (ТОВ «ДКС Центр», 2023)
Abstract. Accounting for grant agreements is an important aspect of financial management for a variety of organisations, including not-for-profit, commercial enterprises, and public institutions. Accounting for grants helps to ensure financial openness and transparency in the organisation's activities. This is important to meet the requirements of stakeholders, including donors, government agencies, investors, and the public. The purpose of the study is to identify the areas of grant funds reporting in accordance with international financial reporting standards. The study found that many organisations receive grants from various sources, and this may include funds from governmental organisations and international donors. Grant accounting helps ensure compliance with the terms of the grant agreement accompanying the grant. Grants accounting helps organisations to effectively manage financial resources provided for specific projects or programmes. This ensures the efficient use of funds and the achievement of planned results. In addition, grant accounting allows you to evaluate the results and impact of projects that have been funded by grants. This helps organisations and donors understand how successful their investments have been. In general, grant accounting is important for the financial stability, transparency, and efficiency of grant-receiving organisations. It helps ensure effective management of financial resources and fulfilment of obligations to donors and other stakeholders.The article provides a detailed classification of types of grants and describes their characteristics. The main provisions regarding the accounting of grants in accordance with IAS 20 have been defined.The use of international standards for grant accounting helps create consistent and comparable financial reporting. It also ensures the quality of financial management and compliance with legislative and regulatory requirements for the organization's financial activities. Grant reporting is a key element that reflects the accurate assessment and effectiveness of the use of grant funds. Ensuring clarity, accuracy, and timely grant accounting is essential for effective management decisions and successful project or program implementation.

Резюме. Бухгалтерський облік грантових угод є важливим аспектом фінансового менеджменту для різних суб’єктів господарювання, у тому числі некомерційних, комерційних підприємств і державних установ. Облік грантів допомагає забезпечити фінансову відкритість і прозорість діяльності організації загалом. Це важливо для задоволення вимог зацікавлених сторін, включаючи донорів, урядових установ, інвесторів і громадськість. Метою дослідження є визначення напрямків звітності про грантові кошти за міжнародними стандартами фінансової звітності. Дослідження показало, що багато господарюючих суб’єктів отримують гранти з різних джерел, зокрема кошти від урядових організацій та міжнародних донорів. Облік грантів допомагає забезпечити дотримання положень та умов грантового договору, що супроводжують грант. Правильне відображення грантів на рахунках бухгалтерського обліку допомагає організаціям якісно управляти фінансовими ресурсами, наданими для конкретних проєктів або програм. Це забезпечує ефективне використання коштів і досягнення запланованих результатів. Крім того, облік грантів дозволяє оцінити результати та вплив проєктів, які були профінансовані за рахунок грантів, що, у свою чергу, допомагає організаціям і донорам зрозуміти, наскільки успішними були їхні інвестиції. Загалом облік грантів важливий для фінансової стабільності, прозорості та ефективності бізнес-структур, що отримують гранти. Це допомагає ефективно управляти фінансовими ресурсами та виконувати зобов'язання перед донорами та іншими зацікавленими сторонами. У статті подано детальну класифікацію видів грантів та описано їх характеристику. Визначено основні положення щодо обліку грантів згідно з МСБО 20. Використання міжнародних стандартів для обліку грантів допомагає створити послідовну та порівнянну фінансову звітність, забезпечує якість управління фінансами та дотримання законодавчих і нормативних вимог до фінансової діяльності організації. Грантова звітність є ключовим елементом, що відображає точну оцінку та ефективність використання грантових коштів. Забезпечення ясності, точності та своєчасного обліку грантів має важливе значення для прийняття ефективних управлінських рішень та успішної реалізації проєкту чи програми.
Державні гранти: обліковий аспект за міжнародними стандартами
Редакційний штат: https://nayka.com.ua/index.php/ee/about/editorialTeam
Зміст: https://nayka.com.ua/index.php/ee/issue/view/119
Keywords: grant agreement; financial statements; government support; social development; business incentives; грантовий договір; фінансова звітність; державна підтримка; соціальний розвиток; стимулювання бізнесу